SOURCE STUDY ANALYSIS OF SUFI OLLOYOR’S WORK “MUROD AL-ORIFIYN” - Uljaev Umarali Qurbanovich (Bright Mind Publishing, 2025)
This paper presents a source-study analysis of Sufi Olloyor’s work “Murod al-Orifiyn” The study examines the historical background of the treatise, its manuscript tradition, and the scholarly interpretations that have shaped its understanding in the field of Islamic studies. Special attention is given to the work’s theological, ethical, and mystical dimensions, as well as its significance within the intellectual heritage of the region. The analysis also highlights the contribution of Sufi Olloyor to the development of spiritual and moral teachings in the broader context of Sufi literature.
Keywords: Sufi Olloyor, Murod al-Orifiyn, manuscript studies, Islamic studies, Sufism, spiritual ethics, source analysis, intellectual heritage.